Home work a memoir of my Hollywood years - Andrews, Julie 1935-; Hamilton, Emma Walton 1962- (Hachette Books, 2019)
With this second memoir, Julie Andrews picks up the story with her arrival in Hollywood and her phenomenal rise to fame in her earliest films -- Mary Poppins and The Sound of Music. Andrews describes her years in the film industry, from the incredible highs to the challenging lows. Not only does she discuss her work in now-classic films and her collaborations with giants of cinema and television, she also unveils her personal story of adjusting to a new and often daunting world, dealing with the demands of unimaginable success, being a new mother, the end of her first marriage, embracing two stepchildren, adopting two more children, and falling in love with the brilliant and mercurial Blake Edwards. The pair worked together in numerous films, including Victor/Victoria, the gender-bending comedy that garnered multiple Oscar nominations
Includes index
Sequel to: Home: A memoir of my early years (2008)
Keywords: Andrews, Julie -- 1935-; Geschichte 1963-1986; Los Angeles- Hollywood; Andrews, Julie; Edwards, Blake / 1922-2010; Motion picture actors and actresses / Great Britain / Biography; Singers / Great Britain / Biography; Singers / United States; BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts; PERFORMING ARTS / Film / General; PERFORMING ARTS / Theater / Broadway & Musicals; Motion picture actors and actresses; Singers; Great Britain; Actors / Biography; Actors; Singers / Biography; Motion picture industry / Los Angeles (Calif.); Motion picture industry; Autobiographies; Biography; Autobiografie